2022
DOI: 10.3390/ijms232113485
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics in Psychiatry Practice: The Value and the Challenges

Abstract: The activity of cytochrome P450 enzymes is influenced by genetic and nongenetic factors; hence, the metabolism of exogenous psychotropic medications and potentially some endogenous neuropeptides is variably affected among different ethnic groups of psychiatric patients. The aim of this review is to highlight the most common cytochrome P450 isoenzymes associated with the metabolism of psychotropic medications (antidepressants, antipsychotics, and mood stabilizers), their variations among different populations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 146 publications
0
1
0
Order By: Relevance
“…This aligns with the recommendations of Siemens et al (2022), who conducted a systematic review of PGx PRS and found large discrepancies between those of candidate gene studies and GWAS, suggesting future studies should be hypothesis-free [ 60 ]. Lastly, as drug metabolism is known to differ by ancestry groups, this study utilized a strict sample of those with European ancestry only, which may increase clinical utility [ 50 , 61 ]. However, we lacked the statistical power to compare individual antipsychotics, which may account for the lack of effect seen in the sensitivity analysis on antipsychotic use as well as on cardiometabolic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with the recommendations of Siemens et al (2022), who conducted a systematic review of PGx PRS and found large discrepancies between those of candidate gene studies and GWAS, suggesting future studies should be hypothesis-free [ 60 ]. Lastly, as drug metabolism is known to differ by ancestry groups, this study utilized a strict sample of those with European ancestry only, which may increase clinical utility [ 50 , 61 ]. However, we lacked the statistical power to compare individual antipsychotics, which may account for the lack of effect seen in the sensitivity analysis on antipsychotic use as well as on cardiometabolic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The CYP2C19 enzyme plays a crucial role in the metabolism of many antidepressants, including selective serotonin reuptake inhibitors (SSRIs) such as sertraline, fluoxetine, citalopram, escitalopram, and others. In addition, multiple conventional tricyclic antidepressants such as imipramine, amitriptyline, trimipramine and clomipramine, are known CYP2C19 substrates ( Alchakee et al, 2022 ). Genetic variations of CYP2C19 significantly impact the efficacy and safety of antidepressant medications, thus clinically influencing depression management.…”
Section: Cyp2c19 In Clinical Practicementioning
confidence: 99%
“…Various CYP450 enzymes are capable of metabolizing more than one drug, and a single drug can be metabolized by multiple CYP enzymes [15]. The activity of these enzymes could be influenced by genetic variations, which may result in individual differences in antidepressant drug metabolism and responses [15,16]. Most genes encoding CYPs are highly polymorphic [19].…”
Section: Cytochrome P450 Familymentioning
confidence: 99%
“…There are four major CYP phenotypes produced by combinations of various alleles with different degrees of enzymatic activity: poor (PM), intermediate (IM), extensive (normal) (EM), and ultrarapid metabolizer (UM). PMs tend to accumulate higher drug levels in the blood and may require lower drug doses to achieve therapeutic effects, whereas UMs may require higher doses due to faster drug elimination [16,17].…”
Section: Introductionmentioning
confidence: 99%